Heidegger's Interpretation of Aristotle's Phronesis and its Implications in Education - Faramarz Muhammadipouya; Poorya Aeini (Pizhūhish/nāmah-i Mabānī-i Ta̒līm va Tarbiyat.)
The main purpose of this study is to explain Heidegger's interpretation of Aristotelian Phronesis and the educational implications based on it. Heidegger considers metaphysics to be a deviation in human thinking, which separated the theoretical from the concrete and practical sphere of human existence and gave priority to it. This deviation has determined all human relationships, including education, which prevents the realization of the original human existence. Heidegger refers to Aristotle's Nicomachean Ethics and interprets the five epistemic states of the human soul with an ontological perspective. Heidegger, unlike Aristotle, believes in the superiority of phronesis as a way of human existence, looking at his concrete sphere, over other aspects. The role of Francis can be seen in Heidegger's discussions about "the meaning of Being", "truth", "Being-in-the-world" and "Dasein". Based on this, the results of analogical reasoning and practical analogy, which have a special place in studies related to education, lose their validity as absolute and certain facts. In real education and training, instead of teaching what is known, the teacher teaches self-learning and teaches them with the position of his inherent being. The authentic human society is open to different possibilities of educational mechanisms and does not consider any situation as the ultimate possibility. As the ultimate level of metaphysical thinking, "Geshtel" reduces everything, including humans, to "resources", and the function of learning theories and curriculum is to make these resources more productive in line with economic interests. Also, Heidegger's thinking provides many possibilities for the development of new conceptualism in the curriculum.